Beyond the fever: shotgun metagenomic sequencing of stool unveils pathogenic players in HIV-infected children with non-malarial febrile illness - Patricia Nabisubi; Stephen Kanyerezi; Grace Kebirungi; Ivan Sserwadda; Mike Nsubuga; Grace Kisitu; Patricia Ntege Nahirya; Bonny Mulindwa; George P. Akabwai; Sylvia Nantongo; Adeodata Kekitiinwa; Edgar Kigozi; et al. (BMC Infectious Diseases)
Abstract Background Non-malarial febrile illnesses (NMFI) pose significant challenges in HIV-infected children, often leading to severe complications and increased morbidity. While traditional diagnostic approaches focus on specific pathogens, shotgun metagenomic sequencing offers a comprehensive tool to explore the microbial landscape underlying NMFI in this vulnerable population ensuring effective management. Methods In this study, we employed shotgun metagenomics to analyse stool samples from HIV-infected children at the Baylor Children’s Clinic Uganda presenting with non-malarial febrile illness. Samples were collected and subjected to DNA extraction at the Molecular and Genomics Laboratory, Makerere University followed by shotgun metagenomics sequencing at the Chan Zuckerberg Biohub San Francisco. Bioinformatics analysis was conducted to identify and characterise the microbial composition and potential pathogenic taxa associated with NMFI using the CZID pipeline. Results Our findings reveal a diverse array of microbial taxa in the stool samples of HIV-infected children with NMFI. Importantly, shotgun metagenomics revealed potentially pathogenic players including Trichomonas vaginalis, Candida albicans, Giardia, and Bacteroides in stool from this patient population. This sheds light on the complexities of microbial interactions that potentially underpin non-malarial febrile illness in this group. Taxonomic profiling identified recognised pathogens and comorbidities and revealed possible new correlations with NMFI, shedding light on the pathophysiology of fever in HIV-infected children. Conclusion Shotgun metagenomics is a valuable method for understanding the gut microbial landscape of NMFI in HIV-infected children, providing a comprehensive approach to pathogen identification and characterisation. By revealing potential pathogenic actors beyond the fever, this work demonstrates how metagenomic sequencing may improve our knowledge of infectious illnesses in vulnerable groups and inspire targeted therapies for better clinical care and outcomes.